Structural and Antifungal Characterization of Co(II), Ni(II) and Cu(II) Complexes with Schiff Bases - RAI, B.K.; BALUNI, AKHILESH; PRASAD, ANUKUL; THAKUR, R.; PRAKASH, PREM (Asian Journal of Chemistry, 2010)
Complexes of the type [M(ANFTS)2]X2 where ANFTS = 2-acetyl naphtho[2-1-b]furan thiosemicarbazone, M = Co(II), Ni(II) and Cu(II); X = Cl–, Br–, I–, NO3– and ClO4–; have been synthesized and characterized on the basis of elemental analysis, molar conductance, magnetic moment, thermal analysis, IR and electronic spectral data. The results are in consistent with tridentate chelation of ligand with azomethine N, oxygen atom of the furan ring of the ligand and thione sulphur atom of thiosemicarbazone as bonding sites as inferred from IR spectra while the complexes of above stoichiometry are proposed to be octahedral environment. The high value of molar conductance suggests the complexes are found to be electrolytic in nature of the 1:2 type.